Realization of nth-order current transfer function using current-differencing buffered amplifiers - Acar, C; Sedef, H (TAYLOR & FRANCIS LTD, 2003)
The authors propose two new configurations suitable for high-order filter response. It is possible to realize the most general n th-order current-mode transfer function using these configurations, involving a single or two current-differencing buffered amplifiers (CDBAs) and the RC:-RC decomposition technique. With the proposed configurations, the number of active elements is reduced to one or two, which is a significant reduction in comparision with the previously reported methods.
Keywords: FILTERS; CDBAS; Engineering